A STOCHASTIC FRONTIER ANALYSIS TO EXAMINE RESEARCH PRIORITIES FOR GENETICALLY ENGINEERED PEANUTS. (27th May 2015) - AFFUSO, ERMANNO; HITE, DIANE; WILSON, NORBERT W.L.
Abstract Pesticide applications are essential for peanut production to control insects, weeds, and other plant pathogens and for a profitable operation. We use a stochastic frontier analysis/primal system approach to test the hypothesis of the overuse of fungicides among peanut farmers. With nationally representative data available from the Agricultural and Resource Management Survey, we find evidence that U.S. peanut growers used excessive amounts of fungicides to prevent fungal infections. If those farmers adopt a new cultivar resistant to fungal pathogens, they could reduce the total cost of chemicals up to 36.2%. The reduction in fungicide use would have spillover environmental benefits.